Integration of aeromedicine in the response to the COVID‐19 pandemic. Issue 4 (4th June 2020) - Osborn, Lesley; Meyer, David; Dahm, Paul; Ferguson, Brandy; Cabrera, Rodolfo; Sanger, Damon; Mock, Michael; Herrera, Tony; Mader, Shelby; Ostrosky‐Zeichner, Luis
Abstract: There is limited guidance on the use of helicopter medical personnel to facilitate care of critically ill COVID‐19 patients. This manuscript describes the emergence of this novel virus, its mode of transmission, and the potential impacts on patient care in the unique environment of rotor wing aircraft. It details the development of clinical and operational guidelines for flight crew members. This allows other out‐of‐hospital clinicians to utilize our framework to augment or supplement their own for the current response effort to COVID‐19. It further serves as a road map for future response to the care of high consequence infectious disease patients.